Survival of Ascaris eggs and hygienic quality of human excreta in Vietnamese composting latrines - Dalsgaard Anders; Klank Lise T; Konradsen Flemming; Phuc Pham D; Jensen Peter KM (BMC, 2009)
Abstract Background For centuries farmers in Vietnam have fertilized their fields with human excreta collected directly from their household latrines. Contrary to the official guideline of six-month storage, the households usually only store human excreta for three to four months before use, since this is the length of time that farmers have available to produce fertilizer between two cropping seasons. This study aimed to investigate whether hygienically safe fertilizer could be produced in the latrines within this period of time. Methods By inoculating eggs of the helminth parasite indicator Ascaris suum into heaps of human excreta, a die-off experiment was conducted under conditions similar to those commonly used in Vietnamese latrines. Half a ton of human excreta was divided into five heaps containing increasing concentrations of lime from 0% to 11%. Results Regardless of the starting pH, which varied from 9.4 to 11.6, a >99% die-off of eggs was obtained after 105 to 117 days of storage for all lime concentrations and 97% of eggs were non-viable after 88 days of storage. The most critical parameter found to determine the die-off process was the amount of ammonia (urine) in the excreta which indicates that longer storage periods are needed for parasite egg die-off if urine is separated from the excreta. Conclusion By inactivating >99% of all A. suum eggs in human excreta during a storage period of only three months the commonly used Double Vault Composting (DVC) latrine, in which urine is not separated, could therefore potentially provide a hygienic acceptable fertilizer.